Pengenalan Kewirausahaan Untuk Siswa Siswi Paket C PKBM Belajar Pintar Kota Padang - Khairil Azmi; Muhammad Jamil; Nardiman Nardiman (Institut Nalanda, 2023)
The Center for Community Learning Activities (PKBM) is an institution established by the community for people engaged in education. PKBM has now become a forum or facilitator for meetings between learning needs and resources, a meeting facilitator between people with learning needs and learning resources so that learning events occur. The implementation of this service is to provide an introduction to the science of entrepreneurship to PKBM students so that later after completing their education at PKBM the students already have what business provisions are suitable to start when completing education at this PKBM. The methods used in this activity are lectures, questions and answers and simulations. Based on this, the solution given to students at PKBM is to provide material and an introduction to the tricks of starting and developing a business so that they are able to take advantage of existing business opportunities